2015
DOI: 10.1093/nar/gkv437
|View full text |Cite
|
Sign up to set email alerts
|

antiSMASH 3.0—a comprehensive resource for the genome mining of biosynthetic gene clusters

Abstract: Microbial secondary metabolism constitutes a rich source of antibiotics, chemotherapeutics, insecticides and other high-value chemicals. Genome mining of gene clusters that encode the biosynthetic pathways for these metabolites has become a key methodology for novel compound discovery. In 2011, we introduced antiSMASH, a web server and stand-alone tool for the automatic genomic identification and analysis of biosynthetic gene clusters, available at http://antismash.secondarymetabolites.org. Here, we present ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
1,584
1
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 1,696 publications
(1,646 citation statements)
references
References 26 publications
14
1,584
1
22
Order By: Relevance
“…The specificity of individual biosynthetic enzymes determines which building blocks will be incorporated into the compound and how it will be modified. The knowledge on enzyme specificity can be used to predict the resultant compounds (Weber et al ., 2015). …”
Section: General Principles Of Antibiotic Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of individual biosynthetic enzymes determines which building blocks will be incorporated into the compound and how it will be modified. The knowledge on enzyme specificity can be used to predict the resultant compounds (Weber et al ., 2015). …”
Section: General Principles Of Antibiotic Biosynthesismentioning
confidence: 99%
“…The vast amount of DNA data available these days provides a large pool of potential compounds encoded in these genomes that, given the bioinformatics tools that exist, are relatively fast and easy to screen for almost no costs. Moreover, sophisticated web‐based tools, such as anti‐SMASH (Medema et al ., 2011; Blin et al ., 2013, 2014; Weber et al ., 2015), PRISM (Skinnider et al ., 2015) or NaPDoS (Ziemert et al ., 2012), are easily accessible and do not require extended expertise in natural product biosynthesis or bioinformatics. Mining bacteria for their genetic potential also revealed that many more bacteria have the ability to produce natural products than previously thought and that more chemical diversity is waiting for discovery.…”
Section: Novel Approaches For Drug Discoverymentioning
confidence: 99%
“…16 The analysis of gifted status among a wide range of microbes with finished genome sequences was carried out by using the standard antiSMASH 3.0 algorithm. 16,31 However, the quality and reliability of antiSMASH 3.0 analysis is limited by the quality of genome seqeuences analyzed. In this report, I demonstrate that the large SMGCs encoding daptomycin, spinosad and tylosin were assembled incorrectly in draft genome sequences, and that draft genomes generally tend to have fragmented assemblies of NRPS-PKS-I gene clusters, resulting overestimation of cluster numbers by antiSMASH 3.0.…”
Section: Discussionmentioning
confidence: 99%
“…4 This major shortcoming limits the utility of antiSMASH 3.0 31 and other bioinformatics tools that require high-quality finished genome sequences for reliable predictions, 16 as further demonstrated below.…”
Section: Assembly Of Nrps and Pks-i Mega-genes In Draft Genome Sequencesmentioning
confidence: 99%
See 1 more Smart Citation